Familial prion disease in a Hungarian family with a novel 144-base pair insertion in the prion protein gene. Issue 3 (16th February 2007) - Kovács, T; Beck, J A; Papp, M I; Lantos, P L; Arányi, Z; Szirmai, I G; Farsang, M; Stuke, A; Csillik, A; Collinge, J
Abstract : About 15% of human prion diseases are inherited, and are associated with point or insertional mutations of the prion protein gene ( PRNP ). Four families with six octapeptide repeat insertions (OPRI) in the PRNP gene have been described in the literature so far. Here we report two cases in a Hungarian family with a new six OPRI (R1R2R2R3R2R3gR3R2R2R3R4) in the PRNP gene. The clinical features (progressive ataxia, dementia and anosmia), the age of onset and the duration of disease were almost identical. In addition to the cerebellar and parahippocampal pathological changes already described, we also found deposits of pathological prion protein in the olfactory system.